Optimization of Casing Design for Complex-Structure Wells - Liu, Xuyang (International Journal of Natural Resources and Environmental Studies, 2024)
This study aims to address the technical challenges encountered during drilling and completion of complex-structure wells, improving the efficiency and safety of casing design. Complex-structure wells, such as horizontal wells, multilateral wells, and extended-reach wells, impose higher demands on casing design due to their intricate geological conditions. Traditional design methods, often reliant on empirical formulas and simplified assumptions, struggle to meet the evolving needs of modern drilling technology. Therefore, this research is dedicated to developing a novel optimization method for casing design in complex-structure wells to enhance drilling efficiency and economic benefits. The study employs a combination of numerical simulation and optimization algorithms. Initially, a comprehensive mathematical model is established, factoring in formation properties, drilling fluid performance, and borehole stability, to forecast drilling performance under various casing designs. Genetic algorithms are then utilized to optimize casing parameters, seeking the optimal casing design that meets safety and economic constraints. The effectiveness of the optimized solution is validated through field trial data and compared against conventional design methods. It is found that the optimized casing design significantly reduces drilling risks, accelerates drilling speed, and cuts drilling costs. Specifically, under the premise of maintaining borehole stability, the optimized scheme decreases drilling time by an average of 15% and reduces drilling costs by approximately 10%. Moreover, the proposed method exhibits strong adaptability, capable of being flexibly adjusted according to different well types and geological conditions, providing a robust technical foundation for efficient drilling of complex-structure wells.